HUKUM PERJANJIAN BUY BACK GUARANTEE TERHADAP KREDIT KEPEMILIKAN RUMAH - Nisa, Ayu Chairun (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2025)
ABSTRACT According to Law No. 1 of 2011 on Housing and Residential Areas, a house functions as a decent place to live, a means of family development, a reflection of the occupants’ dignity, and an asset of the owner. In addition, housing and residential development supports economic growth through job creation and capital formation. The research applied in this study uses a normative approach, which is a form of legal research conducted by examining various literature sources or secondary data as the basis for analyzing statutory provisions. In the implementation of credit agreements, the most commonly used collateral consists of land and buildings or houses. Banks generally require consumers/debtors to submit part of their assets as collateral to ensure debt repayment in the event that the debtor fails to fulfill their obligations at the end of the agreement period. Collateral serves as an additional guarantee required in the provision of credit facilities. In home ownership loans (KPR), the object used as collateral is the house to be purchased by the customer. Therefore, it can be concluded that a buy-back guarantee agreement constitutes a contractual relationship between the bank and the developer cooperating in the distribution of credit funds. This credit agreement generally contains various general provisions regarding housing or property financing, including the loan amount, interest rate, credit term, installment amount, related fees, as well as the rights and obligations of each party. In practice, cases of non-performing KPR loans frequently occur due to the customer’s failure to fulfill their obligations. ABSTRAK Menurut UU No. 1 Tahun 2011, tentang Perumahan dan Kawasan Pemukiman, rumah berfungsi sebagai tempat tinggal layak, sarana pembinaan keluarga, cerminan martabat penghuninya, sekaligus aset pemilik. Selain itu, perumahan dan pemukiman mendukung ekonomi melalui penyediaan lapangan kerja dan pembentukan modal. penelitian yang diterapkan adalah pendekatan normatif, yaitu bentuk penelitian hukum yang dilakukan dengan menelaah berbagai sumber kepustakaan atau data sekunder sebagai dasar untuk menganalisis ketentuan perundang-undangan. Dalam pelaksanaan perjanjian kredit, jaminan yang paling sering dipakai adalah tanah dan bangunan atau rumah. Bank umumnya meminta Konsumen/Debitur menyerahkan sebagian harta kekayaannya sebagai jaminan untuk memastikan pelunasan utang apabila Debitur tidak memenuhi kewajibannya pada akhir masa perjanjian. Agunan menjadi jaminan tambahan yang dibutuhkan dalam pemberian fasilitas kredit. Dalam kredit pemilikan rumah (KPR), objek yang dijadikan jaminan adalah rumah yang akan dibeli oleh nasabah. Maka disimpulkan bahwa perjanjian buy back guarantee merupakan bentuk perikatan antara pihak bank dan pengembang (developer) yang bekerja sama dalam penyaluran dana kredit. Perjanjian kredit ini umumnya memuat berbagai ketentuan umum mengenai pembiayaan rumah atau properti, termasuk jumlah pinjaman, suku bunga, jangka waktu kredit, besaran cicilan, biaya terkait, serta hak dan kewajiban masing-masing pihak. Dalam praktiknya, sering terjadi kredit KPR yang mengalami kemacetan karena nasabah gagal memenuhi kewajibannya.